The Role of Electricity Prosumers in the Increase in the Production of Renewable Energy in Poland - Agnieszka MAZUREK-CZARNECKA (Communications of International Proceedings, 2021)
The aim of the article is an attempt to present the role of prosumers generating electricity in photovoltaic (PV) micro-installations in the growth of installed capacity in renewable energy sources in Poland. The article hypothesized that the mechanisms to support renewable energy sources contributed to a significant increase in new PV prosumer installations in Poland in 2020-2021. The first part of the article refers to the essence of sustainable energy development in Poland. The next section presents the definition of an electricity prosumer in Poland. The article also presents the original division of support mechanisms and briefly presents the instruments used within them. The next part of the article presents the development of prosumer photovoltaic micro-installations in Poland. The article uses the desk research method, which consists in analyzing aggregated data from secondary sources.
Keywords: Renewable energy sources; sustainable development; sustainable development of energy; photovoltaic micro-installations; prosumer; support mechanisms